Contribuição do Método Pilates na dor lombar crônica específica e não específica: uma revisão sistemática e elaboração de um aplicativo móvel em saúde sobre exercícios de pilates para dor lombar crônica - Pires, Larissa Cinara Brunnquell (Universidade do Vale do Rio dos Sinos, 2015)
Low back pain is the second most common cause of general medical consultations, which makes it a very common health issue in the current society. 65% to 80% of the world population will develop an episode of back pain at some point of life, but with spontaneous resolution of the case. Among several current existing exercise programs to the prevention and treatment of lower back pain the Pilates Method is highlighted created by German Joseph Humbertus Pilates. The purpose of this work was to verify that the Pilates method reduces pain in adults with chronic low back pain specific and nonspecific and develop a mobile application with demonstration of Pilates Method’s most effective exercises for the low back pain treatment in adults. Methodology: Considering the possible benefit that Pilates Method can generate for the improvement of the chronic low back pain, one conducted a systematic review through the national and international researches analysis published until January 2014, which investigated the use of Method Pilates’ exercises in patients with lumbar pain. The search for studies used the following databases: Medline through PubMed interface, PEDro, Capes, Cochrane Library and Science Direct. One assessed the methodological quality through PEDro scale. Results: One has found 17 articles, with three systematic reviews and 14 empirical articles. The treatment was performed with exercises based on Pilates Method compared with minimal intervention (they maintained their daily activities) and general exercises (cycling; stretching; posture). These studies suggest that Method Pilates’ exercises in treatment of lumbar pain can help to reduce pain in individuals with low back pain compared to those who did not suffer minimal intervention and to the other exercise programs. The scores of the methodological quality by PEDro scale has ranged from two to eight points in a scale of zero to ten points. Conclusion: The studies included in this systematic review suggest that Pilates Method is effective in reducing short-term lumbar pain and it can be an alternative treatment to low back pain’s cases. Although effective, the treatment results for low back pain through this method is similar to other treatment forms, because other regular physical activities that work abdominal and lower limb strengthening (MMII) promote pain reduction. However, the advantage of Pilates Method is that besides pain reduction, it can improve flexibility and proprioception, reflecting in life quality of patients.
Keywords: Dor lombar; Pilates; Revisão sistemática; Aplicativo; Educação em saúde; Low back pain; Pilates; Systematic review; Application; Health education; ACCNPQ::Ciências da Saúde::Enfermagem